Contribution à L'Etude d'une Plateforme Expérimentale d'un Système de Pompage à Base des Energies Renouvelables - Djihane Naoui (My University, 2025)
This experimental work focused on evaluating a water pumping system intended for use in remote areas, powered by renewable energy sources. The main objective was to ensure reliable and autonomous water pumping under real conditions, through a test bench set up in a university laboratory. The tests demonstrated that water pumping using wind energy, through a permanent magnet synchronous generator, delivered good performance with a stable flow rate proportional to the rotational speed. This system proved effective in powering a pump motor and maintaining an appropriate water flow. In contrast, the tests using photovoltaic panels revealed several limitations, mainly due to the use of an unsuitable inverter (square wave signal) and insufficient current during periods of variable sunlight. These issues affected the stability of the pumping process, particularly during motor startup. This project highlights the feasibility of an autonomous water pumping system based on renewable energy sources, while also emphasizing the need for proper sizing and high-performance equipment to ensure optimal operation. -------------------------------------------------------------------------- ركز هذا العمل التجريبي على تقييم نظام ضخ المياه موجه للمناطق المعزولة، بالاعتماد على مصادر الطاقات المتجددة كمصادر تغذية. تمثل الهدف الرئيسي في ضمان عملية ضخ موثوقة وذاتية التشغيل في ظروف حقيقية، من خلال منصة اختبار أُنشئت في مختبر جامعي .أظهرت التجارب أن ضخ المياه باستخدام الطاقة الريحية، من خلال مولد تزامني مزود بالمغانط الدائمة، يوفر أداءً جيدًا مع تدفق مستقر يتناسب طرديًا مع سرعة الدوران. وقد أثبت هذا النظام فعاليته في تشغيل محرك المضخة وضمان تدفق مناسب للمياه. أما التجارب باستخدام الألواح الشمسية فقد أظهرت بعض القيود، خاصة بسبب استخدام عاكس غير مناسب (إشارة موجة مربعة)، وضعف التيار الكهربائي الناتج خلال فترات ضعف الإشعاع الشمسي. وقد أثرت هذه العوامل على استقرار عملية الضخ، خاصةً عند بدء تشغيل المحرك. يُبرز هذا المشروع إمكانية تنفيذ نظام ضخ مياه ذاتي التشغيل يعتمد على الطاقات المتجددة، مع التأكيد على ضرورة التهيئة الجيدة للنظام واستخدام معدات ذات كفاءة عالية لضمان التشغيل الأمثل ------------------------------------------------------------------------- –Ce travail expérimental a porté l’évaluation d’un système de pompage d’eau destiné aux sites isolés, en s’appuyant sur des énergies renouvelables comme sources d’alimentation. L’objectif principal était d’assurer un pompage fiable et autonome, en conditions réelles, à partir d’un banc d’essai mis en place dans un laboratoire universitaire. Les essais ont montré que le pompage d’eau via l’énergie éolienne, grâce à une génératrice synchrone à aimants permanents, offre de bonnes performances avec un débit stable, proportionnel à la vitesse de rotation. Ce système s’est révélé efficace pour alimenter un moteur de pompe et assurer un débit d’eau adapté. En revanche, les essais avec les panneaux photovoltaïques ont révélé certaines limites, principalement dues à un onduleur non adapté (signal carré) et à un courant insuffisant en cas d’ensoleillement variable. Ces contraintes ont impacté la stabilité du pompage, surtout au démarrage. Ce projet met en évidence la faisabilité d’un système de pompage autonome basé sur les énergies renouvelables, tout en soulignant la nécessité d’un dimensionnement adéquat et d’un matériel performant pour garantir un fonctionnement optima
Keywords: water pumping; isolated site; renewable energy; autonomous system; wind generator; photovoltaic panel; test bench; flow rate; asynchronous motor.; ضخ المياه، موقع معزول، طاقة متجددة، نظام ذاتي التشغيل، مولد ريحي، لوح شمسي، منصة اختبار، معدل التدفق، محرك غير تزامني; pompage d’eau; site isolé; énergie renouvelable; système autonome; génératrice éolienne; panneau photovoltaïque; banc d’essai; débit; moteur asynchrone